The refutation of the self in Indian Buddhism : Candrakīrti on the selflessness of persons - Duerlinger, James; Candrakīrti. (New York : Routledge, 2013)
"Since the Buddha did not fully explain the theory of persons that underlies his teaching, in later centuries a number of different interpretations were developed. This book presents one of these interpretations by the celebrated Indian Buddhist philosopher, Candrakīrti (ca. 570-650 C.E.). Candrakīrti's theory is part of the "Introduction to the Middle Way" ("Madhyamakāvatāra"), which is the central treatise upon which the Madhyamaka (Middle Way) School of Indian Buddhist philosophy was developed. In this book, the text is translated and provided with an introduction and commentary, which offers a careful analysis and historical context on Candrakīrti's account of the selflessness of persons. A philosophical analysis of an ancient Indian philosophical text that is both philologically precise and analytically sophisticated, this book is of interest to scholars of Buddhism generally and Buddhist philosophy"--
Includes bibliographical references and index.
Description based on metadata supplied by the publisher and other sources.
Electronic reproduction. Santa Fe, Arg.: elibro, 2020. Available via World Wide Web. Access may be limited to eLibro affiliated libraries.
Keywords: Candrakīrti.; Mādhyamika (Buddhism); Anātman.; Electronic books